1981
DOI: 10.1159/000182014
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Factor XIII Levels in Children with Renal Disease

Abstract: Plasma levels of coagulation factor XIII determined quantitatively were found to have a tendency to be decreased in more severely affected cases of acute poststreptococcal glomerulonephritis and Henoch-Schönlein nephritis, and found to be decreased in patients with rapidly progressive glomerulonephritis and chronic renal failure in comparison with normal controls. It seems that the degree of decrease in factor XIII reflects the intensity of glomerular damage. In contrast, the patients with the nephrotic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, we cannot definitively confirm the effectiveness of F XIII concentrate administration in preventing the renal involvement in HSP, because only 14 patients in our study received this treatment. Yoshioka et al [20] reported that the F XIII activity decreased in children with acute poststreptococcal glomerulonephritis, HSP nephritis and rapidly progressive glomerulonephritis. Kamitsuji et al [21] showed the deposition of F XIII in the glomeruli of children with various renal diseases including HSP nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot definitively confirm the effectiveness of F XIII concentrate administration in preventing the renal involvement in HSP, because only 14 patients in our study received this treatment. Yoshioka et al [20] reported that the F XIII activity decreased in children with acute poststreptococcal glomerulonephritis, HSP nephritis and rapidly progressive glomerulonephritis. Kamitsuji et al [21] showed the deposition of F XIII in the glomeruli of children with various renal diseases including HSP nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Kamitsuji et al [21] showed the deposition of F XIII in the glomeruli of children with various renal diseases including HSP nephritis. Decreased F XIII activity may thus result from the enhanced fibrin formation in the kidney [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotic syndrome is characterized by edema, proteinuria, and hypoalbuminemia. 28 It can be classified as congenital, primary (minimal change), or secondary (other renal disorders). The etiology of NS includes minimal change, congenital, focal glomerulonephritis, and other categories.…”
Section: Nephrotic Syndrome (Ns)mentioning
confidence: 99%